Aspirin Compared to Low Intensity Anticoagulation in Patients with Non-Valvular Atrial Fibrillation. A Systematic Review and Meta-Analysis. - Fernando J Vazquez; Joaquín P Gonzalez; Esteban Gándara (PLoS ONE)
Background Despite its lack of efficacy, aspirin is commonly used for stroke prevention in atrial fibrillation. Since prior studies have suggested a benefit of low-intensity anticoagulation over aspirin in the prevention of vascular events, the aim of this systematic review was to compare the outcomes of patients with non-valvular atrial fibrillation treated with low-intensity anticoagulation with Vitamin K antagonists or aspirin. Methods We conducted a systematic review searching Ovid MEDLINE, Embase and the Cochrane Central Register of Controlled Trials, from 1946 to October 14th, 2015. Randomized controlled trials were included if they reported the outcomes of patients with non-valvular atrial fibrillation treated with a low-intensity anticoagulation compared to patients treated with aspirin. The primary outcome was a combination of ischemic stroke or systemic embolism. The random-effects model odds ratio was used as the outcome measure. Results Our initial search identified 6309relevant articles of which three satisfied our inclusion criteria and were included. Compared to low-intensity anticoagulation, aspirin alone did not reduce the incidence of ischemic stroke or systemic embolism OR 0.94 (95% CI 0.57-1.56), major bleeding OR 1.06 (95% CI 0.42-2.62) or vascular death OR 1.04 (95% CI 0.61-1.75). The use of aspirin was associated with a significant increase in all-cause mortality OR 1.66 (95% CI 1.12-2.48). Conclusion In patients with non-valvular atrial fibrillation, aspirin provides no benefits over low-intensity anticoagulation. Furthermore, the use of aspirin appears to be associated with an increased risk in all-cause mortality. Our study provides more evidence against the use aspirin in patients with non-valvular atrial fibrillation.